Design and optimization of enzymatic activity in a de novo β‐barrel scaffold. (26th October 2022) - Kipnis, Yakov; Chaib, Anissa Ouald; Vorobieva, Anastassia A.; Cai, Guangyang; Reggiano, Gabriella; Basanta, Benjamin; Kumar, Eshan; Mittl, Peer R.E.; Hilvert, Donald; Baker, David
Abstract: While native scaffolds offer a large diversity of shapes and topologies for enzyme engineering, their often unpredictable behavior in response to sequence modification makes de novo generated scaffolds an exciting alternative. Here we explore the customization of the backbone and sequence of a de novo designed eight stranded β‐barrel protein to create catalysts for a retro‐aldolase model reaction. We show that active and specific catalysts can be designed in this fold and use directed evolution to further optimize activity and stereoselectivity. Our results support previous suggestions that different folds have different inherent amenability to evolution and this property could account, in part, for the distribution of natural enzymes among different folds.